The Effect of Anethum graveolen seed extract on Intestinal Function after cesarean section: a single-blind randomized clinical trial - Zohreh Yousefi; Sedigheh Yousefzadeh; Seyede Houra Mousavi Vahed; Shokouh Sadat Hamedi (Mashhad University of Medical Sciences, 2021)
Introduction: Many women suffer from bloating and abdominal distension after cesarean section. This study was performed with aim to investigate the effect of Anethum graveolenseed extract on intestinal function after cesarean section. Methods: This single-blind clinical trial study was performed on 80 cesarean section women in the hospitals of Mashhad University of Medical Sciences in 2019. Pregnant women were divided into intervention and control groups. The intervention group received Anethum graveolenseed extract 4 hours after cesarean section. Intestinal function was measured before the intervention up to 12 hours after cesarean section. It was measured using visual scale of bloating, tape meter and check list containing the first time of hearing intestinal sounds, flatulence and excretion. For the control group, only the intestinal function was measured as the intervention group. Data were analyzed using SPSS software (version 24) and Mann-Whitney, independent t, Chi-square, and Fisher's exact tests. P<0.05 was considered statistically significant. Results: Mean of intensity of bloating was significantly different between the intervention and control groups (p<0.001). There was no statistically significant difference between the two groups in mean scores of abdominal distension (p<0.05). The mean time of hearing first intestinal sounds, flatulence and excretion after the surgery was significantly different between the intervention and control groups (p<0.001). Conclusion: Consumption of dill seed drops improves the intestinal function after cesarean section.